Yes, Jesus loves me! Mortality salience increases positivity in implicit and explicit images of Christ. - Arrowood, Robert B.; Cox, Cathy R.; Silver, Christopher F. (Mental Health, Religion & Culture, 2023)
The present research, utilising a terror management theory perspective, examined the effects of death awareness on Christians' explicit and implicit image of Jesus. Following exposure to mortality salience, participants were asked to complete a reverse correlation task (Study 1) or a forensic sketch task (Study 2) in an attempt to create an image of Christ. All composites were coded on multiple emotional dimensions (i.e., disgust, contempt, neutrality, happiness, fear, sadness, anger, & surprise). Across studies, the results revealed that participants primed with death created more overtly positive images of Jesus (i.e., less implicit anger, contempt, disgust; more happiness; greater explicit contempt). These findings suggest that a benevolent Christ serves as part of Christians' religious worldviews. A positive Jesus may thus function by protecting individuals against existential anxieties associated with the awareness of death.